Influence of Gut Microbiota on Progression to Tuberculosis Generated by High Fat Diet-Induced Obesity in C3HeB/FeJ Mice - Arias, Lilibeth; Goig, Galo Adrián; Cardona, Paula; Torres-Puente, Manuela; Díaz, Jorge; Rosales, Yaiza; Garcia, Eric; Tapia, Gustavo; Comas, Iñaki; Vilaplana, Cristina; Cardona, Pere-Joan (Frontiers in Immunology, 2019)
The administration of a high fat content diet is an accelerating factor for metabolic syndrome, impaired glucose tolerance and early type 2 diabetes. The present study aims to assess the impact of a high fat diet on tuberculosis progression and microbiota composition in an experimental animal model using a C3HeB/FeJ mouse strain submitted to single or multiple consecutive aerosol infections. These models allowed us to study the protection induced by Bacillus Calmette-Guérin vaccination as well as by the natural immunity induced by chemotherapy after a low dose Mycobacterium tuberculosis infection. Our results show that a high fat diet is able to trigger a pro-inflammatory response, which results in a faster progression towards active tuberculosis and an impaired protective effect of BCG vaccination, which is not the case for natural immunity. This may be related to dysbiosis and a reduction in the Firmicutes/Bacteroidetes ratio in the gut microbiota caused by a decrease in the abundance of the Porphyromonadaceae family and, in particular, the Barnesiella genus. It should also be noted that a high fat diet is also related to an increase in the genera Alistipes, Parasuterella, Mucispirillum and Akkermansia, which have previously been related to dysbiotic processes. As diabetes mellitus type 2 is a risk factor for developing tuberculosis, these findings may prove useful in the search for new prophylactic strategies for this population subset.